1997
DOI: 10.1038/sj.ejcn.1600370
|View full text |Cite
|
Sign up to set email alerts
|

Anthropometric measurements from a cross-sectional survey of community dwelling subjects aged over 90 years of age

Abstract: Objective: To measure anthropometric variables of weight, height, body mass index (BMI) and triceps skin fold thickness (TSF) and produce local percentiles for b 90 y old subjects. To assess prevalence of conventional measures of under nutrition (BMI at or below 18.5 kg/m 2 ) or over nutrition (BMI values b 30 kg/m 2 ) in this age group. Design: Community cross-sectional study. Setting:Belfast, Northern Ireland. Subjects: 238 subjects b 90 y of age who were apparently well, mentally competent and recruited fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
1

Year Published

1998
1998
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 19 publications
0
18
1
Order By: Relevance
“…Female in-patients are at a markedly increased (by more than 3-fold) risk for undernutrition when compared to men (Castel et al, 2006). These findings are in contrast with previous publications reporting similar prevalence rates in elderly men and women (Perissinotto et al, 2002;Rea et al, 1997) or higher rates in men (Ritchie et al, 1997).…”
Section: Nutrients and Food Components In Health And Disease In A Sexcontrasting
confidence: 83%
“…Female in-patients are at a markedly increased (by more than 3-fold) risk for undernutrition when compared to men (Castel et al, 2006). These findings are in contrast with previous publications reporting similar prevalence rates in elderly men and women (Perissinotto et al, 2002;Rea et al, 1997) or higher rates in men (Ritchie et al, 1997).…”
Section: Nutrients and Food Components In Health And Disease In A Sexcontrasting
confidence: 83%
“…Furthermore, anthropometry has also been useful in identifying changes in body size and composition that occur with old age (Chumlea, Rhyne, Garry et al 1989, Lipschitz 1992, Manandhar 1995, Chilima and Ismail 1998, Guo et al 1999. Anthropometri c measurements provide an indirect assessment of body composition and are easy and economical to undertake (Rea, Gillen andClarke 1997, Whitehead andFinucane 1997). Many studies (Burr and Phillips, 1984, Chumlea et al 1986, Shimokata, Tobin, Muller et al 1989, Micozzi and Harris 1990, Yassin and Terry 1991, Delaure et al 1994, Chilima and Ismail 1998, Oguntona and Kuku 2000 have already been reported on health and nutritional status among elderly individuals utilizing anthropometry from di erent parts of the world.…”
Section: Discussionmentioning
confidence: 95%
“…Although various methods to estimate height in the elderly have been developed, their validity remains uncertain. Standing height (stature) is still the most widely used statistic for height measurement in the elderly (Van Staveren et al, 1995;Rea et al, 1997;Finch et al, 1998) and was measured by a standard method in the present study. Table 5 shows that the subjects in the older groups had lower mean statures.…”
Section: Differences Between Age Groupsmentioning
confidence: 99%